High intensity focused ultrasound responsive metallo-supramolecular block copolymer micelles - Liang, Bo (Langmuir : the ACS journal of surfaces and colloids, 2014)
The metal-supramolecular diblock copolymer containing mechano-labile bis(terpyridine)-Cu(II) complex linkage in the junction point was synthesized. These metal-ligand containing amphiphilic copolymers are able to self-assemble in aqueous solution to form spherical micelles with poly(propylene glycol) block forming the hydrophobic core. It is found that high intensity focused ultrasound can open the copolymer micelles and trigger the release of the payload in the micelle. The micellar properties and release kinetics of encapsulated guest molecule in response to ultrasound stimuli were investigated. The weak Cu(II)-terpyridine dynamic bond in the copolymer chain can be cleaved under ultrasound and thus leads to the disruption of the copolymer micelle and the release of loaded cargo. This study will open up a new way for the molecular design of ultrasound modulated drug delivery systems